Management Accounting Information Systems, Performance Measurement Methods and Reward Systems in Influencing Managerial Performance - Udik Jatmiko (International Journal on Social Science, Economics and Art, 2022)
The problem that is the indication of management accounting information system policies, performance measurement methods, and reward systems that are less effective, so that they are felt to affect managerial performance. The number of samples obtained from the total population in as many as 32 people. Data analysis techniques using validity and reliability tests, multiple linear regression tests, t tests and F tests. The results of the research carried out obtained that partially the application of management accounting information systems to managerial performance. The performance measurement method has a positive and significant effect on managerial performance. The reward system has a positive and significant effect on managerial performance. Simultaneously the application of management accounting information systems, performance measurement methods and reward systems have an effect on managerial performance with a significant value of F 0.001 < sig. 0.05. Management should always pay attention to the development of the systems implemented, including the application of management accounting information systems, performance measurement methods and reward systems in order to achieve the effectiveness of managerial performance.